2021
DOI: 10.1159/000521018
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth and Adipose Fat Tissue Trajectories in Twin Pregnancies after Gastric Bypass Surgery

Abstract: Introduction: Previous studies demonstrated a continues decline in fetal growth throughout singleton pregnancy after bariatric surgery. However, intrauterine growth in twin pregnancy is subjected to further underlying processes. This study was to investigate the longitudinal assessment of fetal biometry and abdominal fat thickness of twin pregnancies conceived after gastric bypass surgery and compare them to BMI-matched and obese controls. Materials and methods: We retrospectively assessed ultrasound data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The above studies compared women with obesity after bariatric surgery and women with obesity without surgical treatment, and studies concerned single pregnancies. However, few studies on twin pregnancies have also confirmed the association of bariatric surgery before pregnancy with delayed intrauterine growth of the fetus, as indicated by fetal parameters such as slower growth of subcutaneous fat tissue and abdominal circumference, as well as lower birth weight of the newborn [99].…”
Section: The Influence Of Bariatric Surgery On Pregnancy and Neonatal...mentioning
confidence: 99%
“…The above studies compared women with obesity after bariatric surgery and women with obesity without surgical treatment, and studies concerned single pregnancies. However, few studies on twin pregnancies have also confirmed the association of bariatric surgery before pregnancy with delayed intrauterine growth of the fetus, as indicated by fetal parameters such as slower growth of subcutaneous fat tissue and abdominal circumference, as well as lower birth weight of the newborn [99].…”
Section: The Influence Of Bariatric Surgery On Pregnancy and Neonatal...mentioning
confidence: 99%